A preliminary survey of freshwater snails in selected barangays in San Miguel, Leyte - Opleda, November Lily C.; Varona, Gracia F. (2017)
Gastropods are soft-bodied, single-valve animals of Phylum Mollusca. It is one of the most diverse taxa including over 40,000 species in which 5,000 of these are snails thriving in freshwater habitats. This study aimed to provide a preliminary assessment of the freshwater snails in San Miguel, Leyte. Freshwater snails were collected from three accessible collecting stations within three selected barangays through intensive snail search and random ring sampling on March 2017.
A total of 4526 individual freshwater snails belonging to 8 species from 5 families were collected and identified in San Miguel, Leyte. Three families belonged to Subclass Caenogastropoda (Ampullaridae, Viviparidae, Thiaridae), while the other three belonged to Subclass Heterobranchia (Lymnaeidae, Planorbidae). Radix natalensis (Lymnaeidae) was the predominant freshwater snail species, making up to 34% of all individual snails, followed by Pomacea canaliculata (Ampullaridae) and Melanoides tuberculata (Thiaridae). Neritina pulligera (Neritidae) had the lowest snail count. The snail species were found in habitats with moist substratum, organic matter, and vegetation cover. The diversity is relatively low, with H' values ranging from 0.6785 to 1.832.
Undergraduate thesis (B.S. Biology) --University of the Philippines, Tacloban.